Platelets Direct Monocyte Differentiation Into Epithelioid-Like Multinucleated Giant Foam Cells With Suppressive Capacity Upon Mycobacterial Stimulation - Feng, Yonghong (J Infect Dis, 2014)
Background. Epithelioid, foam, and multinucleated giant cells (MNGCs) are characteristics of tuberculosis granulomas, yet the precise genesis and functions of these transformed macrophages are unclear. We evaluated the role of platelets as drivers of macrophage transformation in mycobacterial infection. Methods. We employed flow cytometry and microscopy to assess cellular phenotype and phagocytosis. Immune assays allowed quantification of cytokines and chemokines, whereas gene microarray technology was applied to estimate global transcriptome alterations. Immunohistochemical investigations of tuberculosis granulomas substantiated our findings at the site of infection. Results. Monocytes differentiated in presence of platelets (MP-Macs) acquired a foamy, epithelioid appearance and gave rise to MNGCs (MP-MNGCs). MP-Macs up-regulated activation markers, phagocytosed mycobacteria, and released abundant interleukin 10. Upon extended culture, MP-Macs shared transcriptional features with epithelioid cells and M2 macrophages and up-regulated CXCL5 transcripts. In line with this, CXCL5 concentrations were significantly increased in airways of active tuberculosis patients. The platelet-specific CD42b antigen was detected in MP-Macs, likewise in macrophages, MNGCs, and epithelioid cells within tuberculosis granulomas, along with the platelet aggregation-inducing factor PDPN. Conclusions. Platelets drive macrophage differentiation into MNGCs with characteristics of epithelioid, foam, and giant cells observed in tuberculosis granulomas. Our data define platelets as novel participants in tuberculosis pathogenesis.